Olfactory and taste dysfunction in coronavirus disease 2019 patients: its prevalence and outcomes. Issue 11 (16th November 2020) - Jain, A; Kumar, L; Kaur, J; Baisla, T; Goyal, P; Pandey, A K; Das, A; Parashar, L
Abstract: Objectives: To evaluate the occurrence, clinical course and outcomes of olfactory and gustatory dysfunction in patients with laboratory confirmed coronavirus disease 2019 infection. Methods: This is a prospective cross-sectional study of patients diagnosed with coronavirus disease 2019 infection by reverse transcription polymerase chain reaction over two months. The epidemiological and clinical outcomes studied were: age, sex, general symptoms, and olfactory and taste dysfunction. Results: A total of 410 coronavirus disease 2019 infected patients were included in the study, with 262 males (63.9 per cent) and 148 females (36.1 per cent). Ninety-nine patients (24.1 per cent) reported chemosensory dysfunction, of which 85 patients (20.7 per cent) reported both olfactory and taste dysfunction. Olfactory and taste dysfunction were proportionally more common in females. The mean duration of olfactory and taste dysfunction was 4.9 days, with a range of 2–15 days. Conclusion: Olfactory and taste dysfunction are prevalent symptoms in coronavirus disease 2019 patients. In this study, they were more common in females than males. The occurrence of such dysfunctions is lower in the Indian population than in the European population.